2021
DOI: 10.1111/1556-4029.14763
|View full text |Cite
|
Sign up to set email alerts
|

Novel extraction chemistry and alternative amplification strategies for use with rootless hair shafts

Abstract: Rootless hair shafts are often considered unsuitable for STR genotyping due to the known high failure rate. The same samples can be reliably processed with mitochondrial sequencing. However, the minimal discriminatory power of widely implemented control region mitochondrial sequencing techniques limits its utility in some forensic casework. In this research, multiple variables were tested to provide information on rootless hair shaft sample genotyping success. Results showed external decontamination procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The differences between the Hair and Bone Kits include different binding and digest buffers, DTT is included only in the Hair kit, and different volumes and incubation times. A previous study confirmed that rootless hairs processed with the InnoXtract Hair method yielded probative autosomal STR and INNUL profiles [45,46].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The differences between the Hair and Bone Kits include different binding and digest buffers, DTT is included only in the Hair kit, and different volumes and incubation times. A previous study confirmed that rootless hairs processed with the InnoXtract Hair method yielded probative autosomal STR and INNUL profiles [45,46].…”
Section: Introductionsupporting
confidence: 59%
“…Cold cases, such as a 1980 Newport Beach murder [29] and a 1977 southern California murder [30] were both solved through hair forensic DNA analysis, where the hair sample was the only evidence available. As forensic DNA testing expands to newer DNA typing techniques (microhaplotype [31], SNP [32,33], SAP [34], InDel [35,36], INNUL [37,38], NGS [39,40], etc.) and new analysis methods, such as forensic genetic genealogy, rootless hairs are increasingly becoming a more probative sample type [41].…”
Section: Introductionmentioning
confidence: 99%